Awareness, perceptions and attitudes toward medication-related osteonecrosis of the jaw among physicians who treat osteoporosis - Suad Aljohani (Elsevier, 2023)
Osteoporosis is the most common indication for antiresorptive drugs (ARDs). Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication of ARDs. Multiple risk factors can increase the risk of MRONJ, one of which is the duration of ARD intake, which is usually prolonged for osteoporosis cases. Prevention of MRONJ relies on collaborative care between treating physicians and dental practitioners. Therefore, knowledge about MRONJ and its prevention strategies is crucial for both teams. Aim: This study aimed to assess the knowledge and attitudes of physicians toward MRONJ in osteoporosis patients. Another aim was to develop recommendations for the prevention of MRONJ. Materials and methods: Through an online survey, basic information such as the practice location, training, knowledge, perceptions, and attitudes of physicians regarding ARDs and MRONJ in osteoporosis patients was collected. Statistical analysis was performed for all variables, and their correlations were explored. Results: A total of 221 physicians participated in the survey: 34.8% were rheumatologists, 25.3% were endocrinologists, 8.6% were family medicine physicians, 5.9% were orthopedists, and 5.9% were internal medicine physicians. Of them, 58.0% reported more than 6 years of experience. Only 78.7% were aware of MRONJ and recognized that bisphosphonates (BPs) can contribute to MRONJ. In contrast, 56.0% recognized denosumab as a causative factor for MRONJ. Duration of ARD therapy and pre- and post-ARD dental care were known to influence the risk of MRONJ by 62% and 65.6% of the participants, respectively. Only 41.6% and 31.2% of participants informed patients about MRONJ prior to BP and denosumab therapy, respectively. Only 25.3% and 20.8% referred patients to dentists before BP and denosumab therapy, respectively. Overall, 65.6% of the participants had a negative attitude toward MRONJ, and 34.4% had a positive attitude. A positive attitude was mostly observed among rheumatologists (55.8%) compared to other specialists (p <0.001). More years of experience were associated with a higher level of knowledge and positive attitude. Conclusion: The findings of this study identified a notable gap in the awareness, knowledge and attitudes of physicians regarding MRONJ in osteoporosis patients. Continuing education programs about ARDs and MRONJ risk are highly recommended.